Improving the indoor air quality (IAQ) through application of the air cleaning technologies for offices building simulated in environmental chamber - Abdelrahman Kabrein, Hashim Ahmed (2017)
Indoor air quality (IAQ) is very important issue in residential and commercial buildings, because human spend almost 90% of their life indoor. IAQ problems effect on the health of the occupants, and lead to reduction of the efficiency and output in workplaces. The main objective of this study is to improving the (IAQ) and to reduce energy consumption in offices building, through experimental and simulation investigation. The method used in this study was by using environmental chamber to represent the real office. The results of the experimental were validated the simulation. The chamber was modified by installing two mechanical filters with low pressure drop; minimum efficiency reporting value rate 13 (MERV 13) and activated carbon filter (ACF) on the air handling unit. The IAQ parameters which include temperature, relative humidity, air velocity, air flow rate, pressure drop, CO2 concentration and particle matters PM 10 and PM 2.5 concentration for upstream and downstream were considered in this study. These variables were measured inside the chamber using IAQ devices and these data were used as an input data for simulation by using ANSYS 16.1 software. The simulation generated the air distribution via air velocity, temperature, CO2 concentration and the particle distribution in the room. The results from experiment showed good agreement for combining filters efficiency value from 86.20% to 84.60% and from 86% to 82.35% for PM 10 and PM 2.5 particle removal respectively during occupied period. The CO2 concentration decreased during the measurement period from 816 ppm to 700 ppm and the distribution was in the acceptable range compare with ASHRAE standard 55-2004 and Malaysian industry code of practice on IAQ. Also, the validation with simulation showed below 10% error ratio compare with experiment results. The significance of study is to balance between enhancing thermal comfort inside workplace and (IAQ) for occupants, leading to reduction of energy consumption.